Theoretical Simulation on a Nonlinear Photonics Process of Er(1%)Yb(8%): FOV Oxyfluoride Nanophase Vitroceramics (Communications in Computational Physics, 2010)
We numerically simulate a photonics phenomenon of what we call intensityinversion between red and green fluorescence in oxyfluoride nanophase vitroceramicsEr(1%)Yb(8%): FOV through the integration of whole fluorescence's theories. Wefound that it is essential to introduce a coefficient presenting the difference betweenthe Stokes energy transfer and anti-Stokes energy transfer processes in nano-materialwhen calculating the energy transfer rate. Under this consideration, and with the totalcrystallized volume ratio set to be 17.6%, the simulation results of the populationprobabilities values of all energy levels of Er3+ ion are coincident with the experimentalresult perfectly.